A new biomarker (RENALASE) for the diagnosis of blunt renal trauma in an experimental study - Sarac, Mehmet; Bakal, Unal; Tartar, Tugay; Aydin, Suleyman; Kuloglu, Tuncay; Akdeniz, Ibrahim; Kazez, Ahmet (Elsevier Sci Ltd, 2021)
Introduction Kidneys are the most frequently injured organ in the genitourinary system, but there is no specific biological marker for this trauma. Renalase may be a descriptive biomarker of the pathology that causes renal ischemia, nephrotoxicity, and acute renal failure. Objective This study investigated the role of serum and urine levels of renalase for the diagnosis of renal injury in rats with experimentally induced blunt renal trauma. Study design Thirty 3-month-old Sprague-Dawley adult male rats were divided into five groups (n = 6) as follows: control (Group 1), sham (Group 2), right nephrectomy (Group 3), left renal trauma (Group 4), and right nephrectomy plus left renal trauma (Group 5). Serum samples were acquired 3, 24 and 48 h post-trauma, and urine samples were acquired between 0-24 and 24-48 h post-trauma. Changes in serum and urine levels of renalase, dopamine, epinephrine, metanephrine, normetanephrine, urea, and creatinine were assessed after blunt renal trauma. Results No significant changes in serum levels of these compounds were observed at 3 h post-trauma in Groups 1 and 2 or in urine collected sequentially at 0-24 and 24-48 h. By contrast, levels of renalase, dopamine, metanephrine, and normetanephrine in serum increased during hour 3 in Groups 4 and 5. Moreover, increases in urine levels of renalase, dopamine, epinephrine, metanephrine, and normetanephrine were observed at hours 0-24 in Groups 4 and 5. Discussion A definitive diagnosis of traumatic renal injury in children is made with contrast-enhanced computed tomography. However, the scan results in high doses of radiation exposure to children. Here, we report for the first time that renalase levels may be useful as a biomarker for the diagnosis of renal injury due to blunt renal trauma. Conclusion Renalase may be a simple, effective, and noninvasive biomarker that indicates traumatic renal injury. It could be used as an adjunct for evaluation, particularly for isolated traumatic renal injury in cases where access to computed tomography is not straightforward.
Keywords: Blunt renal trauma; Renal injury; Early diagnosis; Biomarker; Renalase; Catecholamine